Lemos on the Physical Indeterminism Luck Objection. - Moore, Dwayne (Philosophia, 2023)
I recently argued that reductive physicalist versions of libertarian free will face a physical indeterminism luck objection. John Lemos claims that one potential advocate of reductive physicalist libertarianism, Robert Kane, avoids this physical indeterminism luck objection. I here show how the problem remains.